2012
DOI: 10.1039/c2jm31243c
|View full text |Cite
|
Sign up to set email alerts
|

Template-free synthesis of zinc citrate yolk–shell microspheres and their transformation to ZnO yolk–shell nanospheres

Abstract: A novel, facile, green and template-free approach was developed for the fabrication of amorphous zinc citrate yolk-shell microspheres and crystalline ZnO yolk-shell nanospheres. In this approach, the amorphous zinc citrate yolk-shell microspheres were prepared through a single chemical reaction at low temperature (90 C) and with room temperature ageing. The zinc citrate yolk-shell microspheres have an average size of about 1.25 mm. The average diameter of the inner cores and the average thickness of the outer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 48 publications
1
61
0
Order By: Relevance
“…1A, the XRD pattern of the precursor reveals that the sample contains two phases. One is wurtzite structured ZnO and the other may be the crystalline zinc citrate phase [16]. For a better understanding of the sample, the FT-IR spectrum was performed.…”
Section: Resultsmentioning
confidence: 99%
“…1A, the XRD pattern of the precursor reveals that the sample contains two phases. One is wurtzite structured ZnO and the other may be the crystalline zinc citrate phase [16]. For a better understanding of the sample, the FT-IR spectrum was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, zinc citrate microspheres were first fabricated based on the Ostwald ripening process, which could provide −OH and −COO− functional groups for the adsorption of Ce 3+ ions through electrostatic interactions. After washing, the obtained zinc–cerium citrate hollow microspheres were further transformed into ZnO/CeO x HMS after calcination . The SEM image revealed that the as‐synthesized product was composed of microspheres with an average diameter of about 1.0 μm (Figure b and Figure S1 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…After washing, the obtained zinc-cerium citrate hollow microspheres were further transformed into ZnO/CeO x HMS after calcination. [45] The SEM image revealed that the as-synthesized product was composed of microspheres with an average diameter of about 1.0 mm( Figure 2b and Figure S1 in the Supporting Information). From the magnified image in Figure 2c,i tw as clear that each ZnO/CeO x HMS was made up of numerous nanoparticles with sizes ranging from 5t o2 0nm.…”
Section: Synthesis and Characterization Of Zno/ceo X Hmsmentioning
confidence: 99%
“…Prolonging to 16 h, the thicknesses of shells reach 110 nm while the cores change to approximately 400 nm. This phenomenon could be explained by the Ostwald ripening mechanism related to a progressive reallocation of case from the cores to the shells of the spheres [35]. Concretely, compared with the outer shells, the inner cores exhibit small size and larger curvatures, which would result in a higher energy [36,37].…”
Section: Time-dependent Experiments On Phase and Morphologymentioning
confidence: 99%